Oxymatrine induces apoptosis and inhibits invasion in Gallbladder carcinoma via PTEN/PI3K/AKT pathway - Qian, Liqiang (Cytotechnology, 2017)
Oxymatrine extracted from Sophora flavescens Ait as a natural polyphenolic phytochemical has been demonstrated to exhibit anti-tumor effects on various cancers, including Gallbladder carcinoma (GBC). However, its underlying mechanisms of function are largely unknown in GBC cells. The present study is conducted to investigate the anti-tumor effects and the underlying mechanisms of oxymatrine on GBC cells in vitro and in vivo. The results showed that oxymatrine inhibited cell viability, metastatic ability and induced cell apoptosis in dose-dependent manners. Furthermore, we found that the expression of p-AKT, MMP-2, MMP-9 and the ratio of Bcl-2/Bax were significantly down-regulated, while the expression of PTEN was up-regulated in GBC cells. In addition, pretreatment with a specific PI3K/AKT activator (IGF-1) significantly antagonized the oxymatrine-mediated inhibition of GBC–SD cells. Subsequently, our in vivo studies showed that administration of oxymatrine induced a significant dose-dependent decrease in tumor growth. In conclusion, these findings indicated that the inhibition of cells proliferation, migration, invasion and the induction of apoptosis in response to oxymatrine in GBC cells, may function through the suppression of PTEN/PI3K/AKT pathway, which was considered as the vital signaling pathway in regulating tumorigenesis. These results suggested that oxymatrine might be a novel effective candidate as chemotherapeutic agent against GBC.